2014
DOI: 10.1021/cm500896n
|View full text |Cite
|
Sign up to set email alerts
|

How Robust are Semiconductor Nanorods? Investigating the Stability and Chemical Decomposition Pathways of Photoactive Nanocrystals

Abstract: Anisotropic II-VI semiconductor nanostructures are important photoactive materials for various energy conversion and optical applications. However, aside from the many available surface chemistry studies and from their ubiquitous photodegradation under continuous illumination, the general chemical reactivity and thermal stability (phase and shape transformations) of these materials are poorly understood. Using CdSe and CdS nanorods as model systems, we have investigated the behavior of II-VI semiconductor nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
3
14
0
Order By: Relevance
“…In agreement with that, work performed by Reichert et al showed that CdSe and CdS NRs were compositionally stable up to 700 °C in an inert atmosphere. 44 Our findings and the observations of Hellebusch et al and Reichert et al strengthen our hypothesis that the deformation and chemical transformations upon laser irradiation are not a purely heat-induced effect. Heat was shown to speed up the radiation-induced effects though.…”
Section: Resultssupporting
confidence: 90%
“…In agreement with that, work performed by Reichert et al showed that CdSe and CdS NRs were compositionally stable up to 700 °C in an inert atmosphere. 44 Our findings and the observations of Hellebusch et al and Reichert et al strengthen our hypothesis that the deformation and chemical transformations upon laser irradiation are not a purely heat-induced effect. Heat was shown to speed up the radiation-induced effects though.…”
Section: Resultssupporting
confidence: 90%
“…The activity of the photocatalytic reactions can be enhanced by addition of some inorganic species such as H 2 S 2 and H 2 O 2 (Malinda, Reichert, Chia, and Javier, 2014). Generally, backelectron transfer can reduce the activity of the photocatalyst so the main challenge in this context is how to reduce the rate of recombination reaction which leads consequently to improve the activity of the photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…One dimensional (1D) semiconductor nanostructures such as nanowires, nanotubes, nanobelts and nanorods fabricated by various methods are important both in fundamental research and technological applications, as they present new systems on which chemical and physical interactions among nanocrystals can be investigated [1][2][3][4][5][6][7]. These nanowire and nanorod heterostructures have the potential to revolutionize nanomaterials research by providing means to define multiple functionalities within single nanostructures.…”
Section: Introductionmentioning
confidence: 99%